Analysis of the thermal performance of an uncovered 1-hectare solar pond in Benguela, Angola. (October 2021) - Cardoso, Susana; Mourão, Zenaida; Pinho, Carlos
Abstract: This is the study of the thermal efficiency performance of a possible 1-ha solar pond located at Caota beach, in Benguela, Angola. During the first year of operation there was no energy extraction from the pond and the water temperature in the lowest and denser layer reached 93 °C. From the second year onwards thermal energy was extracted. Two scenarios were adopted, water heating from 40 to 60 °C or water heating from 50 to 70 °C. Yearly 1600 MWh and 700 MWh could be extracted, in the first and or the second scenario. Operating regimes of 8, 12 or 24 h/day were considered. Based on the total pond incident solar energy, the overall energy efficiency of the pond is in the 2 to 5 % range, while the exergy efficiency is in the 0.4 to 2.6 % range. The repartition of the pond energy losses is also quantified.